Coolie Depot, Nelson Island, Trinidad (2011)
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided The postcard shows Nelson Island which belongs to what was thought to be a group of "five islands" but which is actually a group of six islands located west of Port of Spain, the capital of Trinidad, in the Gulf of Paria. Nelson Island was used as the disembarkation point and quarantine station for indentured immigrants who came to Trinidad and Tobago from 1845-1917. Funding for this project has been provided by Mrs. Irma E. Goldstraw.